Analysis of Differences in Student Achievement of Students IAIN Palopo Students by Entry Route Student - Alauddin Alauddin; Arsyad L (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to test whether there are differences in student achievement at IAIN Palopo based on the entrance route. The research was conducted using quantitative methods by distributing questionnaires to 270 respondents. The data were analyzed using the Kruskal Wallis test to see whether or not there were group differences. The results of this study show that there is a significant difference in the learning achievement of IAIN Palopo students based on the entry path, namely between the SPAN and UMPTKIN pathways and the SPAN and Independent pathways. The SPAN entry pathway group ranks highest in learning achievement based on the entry pathway.